Remote work and high proximity employment in Mexico - Lorenzo Aldeco Leo; Alejandrina Salcedo (Banco de México, 2024)
We show that in Mexico larger shares of potential remote work at the municipality level are related to lower post-pandemic employment in high-proximity consumer services, a relatively large sector that mainly employs low-income workers. We use a triple difference event study design where we compare employment in high and low proximity sectors across municipalities with different levels of remote work potential, before and after the pandemic. Our results contribute to explain the relatively weak recovery in high proximity employment in the central region of the country, where at the start of the pandemic a larger proportion of high-proximity services located where remote work potential was high, relative to other regions. The analysis highlights that with the pandemic the sectoral distribution of employment has changed, and that the effects on workers depend on their capacity to adjust to the new labor market.
Keywords: O33; R11; J20; 330; Remote work; Consumer services; Middle-income; Triple-differences